Effect of direct current electric field on the root growth of oil palm seedlings - Detlamasi Agustin; Zamri Zamri; Doni Basdyo; Saktioto Saktioto; Muhammad Safwan Abd Aziz; Mohammed M Fadhali (Science, Technology, and Communication Journal, 2023)
The acceleration of the growth in the rate of oil palm seed roots is a non-chemical solution in nursery needs. Utilizing the electricity sector as an increase in germination productivity. In this case, this study examines variations in the electric field direct current 50, 100, 200, 400, 800, and 1000 V/m and the exposure of time 15, 30, 45, and 60 minutes. The results showed exposure to an electric field direct current in voltage of 100 V/m increased germination at each exposure time by 17%, 21%, 20% and 26% with exposure times of 15, 30, 45, and 60 minutes to control. However, a maximum intensity of 1000 V/m inhibits the germination process for each time of 30, 45, and 60 minutes by 8%, 9%, and 12% in the control. Exposure to direct current in electric field intensity and exposure of time affect root metabolism in the germination process.